ANALISIS FINANSIAL TEKNOLOGI SISTEM TANAM JAJAR LEGOWO PADA USAHATANI PADI DI LAHAN SAWAH IRIGASI - Teguh Prasetyo; Cahyati Setian; Muniri Eti Wulandari (Program Studi Agribisnis Universitas Sumatera Selatan, 2022)
Efforts to maintain the productivity of rice farming land in a sustainable manner by applying location- specific technological innovations. Jarwo technology research aims to determine the productivity andprofits of rice farming. The research method used is to compare Jarwo technology with farmerpatterns in rice farming. Data collection is done by means of periodic observations. The data collectedincludes productivity, output, and input of rice farming. Data were analyzed using evaluation methodand cross tabulation. The results showed that the average productivity of rice using Jarwo technologywas 8.90 tons/ha GKP, while the average yield of rice productivity by farmers was 7.80 tons/ha GKP. Milled dry grain (GKG) with a moisture content of 11-12% in Jarwo technology farming is 6.14 tons/ha, while the average productivity of rice using farmer-pattern technology is 5.23 tons/ha. The labor costof rice farming on Jarwo technology is 66.36% of the total cost, while the labor cost of farmingtechnology is 67.32%. The selling value of GKP rice with Jarwo technology is higher than the farmerpattern. Rice productivity and farming profits with Jarwo technology are considered higher with an R/Cratio value of 3.91, while in farming the R/C ratio is 3.85. Jarwo technology has the potential to bewidely developed, it is recommended that massive dissemination be carried out followed by intensiveassistance, both by formal officers and independently.